Across the Divide : Union Soldiers View the Northern Home Front - Ramold, Steven J. (Book collections on Project MUSE., 2013)
Union soldiers left home in 1861 with expectations that the conflict would be short, the purpose of the war was clear, and public support back home was universal. As the war continued, however, Union soldiers noticed growing disparities between their own expectations and those of their families at home with growing concern and alarm. Instead of support for the war, an extensive and oft-violent anti-war movement emerged. In this first study of the gulf between Union soldiers and northern civilians, Steven J. Ramold reveals the wide array of factors that prevented the Union Army and the civilians on whose behalf they were fighting from becoming a united front during the Civil War. In Across the Divide, Ramold illustrates how the divided spheres of Civil War experience created social and political conflict far removed from the better-known battlefields of the war. -- Book jacket.